Selection of an Appropriate Acid Type for the Recovery of Zinc From a Flotation Tailing by the Analytic Hierarchy Process - Kursunoglu, Sait; Kursunoglu, Nilufer; Hussaini, Shokrullah; Kaya, Muammer (Elsevier Sci Ltd, 2021)
The selection of acid type for metal dissolution from minerals is an important issue in leaching operations. Acids are used to recover valuable elements from the minerals by dissolving them in a solution. The acid must offer a high recovery at marginal cost and a low environmental effect. Many parameters can affect the acid type selection for high leaching recovery and low environmental effect and thus, the selection of an acid type is complex. In this study, based on the experimental results obtained from the bench-scale laboratory studies, the selection of acid type for the recovery of zinc from a flotation tailing was investigated using the analytic hierarchy process (AHP). The utilization of AHP was supported by the use of ExpertChoice (R) 2000 software. The outcomes demonstrated that sulfuric acid is the most desirable acid type with a ranking of 0.541, tracked by citric acid, and oxalic acid with scoring of 0.282 and 0.177, respectively. Furthermore, analyses of sensitivity were performed to examine the influence of the main criteria on the different acid type. It emerged that citric acid can be used when the environmental main criterion ascended from 7.8% to 75.3%. (C) 2020 Elsevier Ltd. All rights reserved.
Kursunoglu, Sait/0000-0002-1680-5482; Kursunoglu, Nilufer/0000-0003-1765-9015; Kaya, Muammer/0000-0001-5260-2589; Hussaini, Shokrullah/0000-0003-0287-0061
Keywords: Acid Type Selection; Flotation Tailing; Zinc; Analytic Hierarchy Process; Sensitivity Analysis